Obelisk - Kapustin, Petr (project baikal, 2018)
The origin of the obelisk is mysterious. Like many other things in the history of our civilization, it occurs at once, perfectly shaped, without genesis or labour pains. Like the Great Pyramids, it appears ‘from nowhere’, in solid stone structures, in monoliths, and then similarly degrades down to bricks, boards and cemetery plaques.